Analisis Karakter Kuantitatif Klon-Klon Krisan (Chrysanthemum morifolium Ramat.) Generasi MV7/8 Hasil Mutasi Sinar Gamma - Khairunissa Islamiati; Ani Lestari; H.M. Yamin Samaullah; Liaw Lia Sanjaya (Jurnal Ilmiah Wahana Pendidikan, 2022)
The development of domestic chrysanthemum cultivation is still faced by several problems, including the limited supply of seeds so that production is not optimal, often the cultivated varieties are still imported, so they cannot compete in the global market. Efforts to reduce dependence on imported varieties, as well as increase the productivity and development of domestic chrysanthemums can be done through plant breeding, one of which is the induction of gamma ray mutations. Mutations have been carried out on various plants and have been proven to be successful in increasing genetic diversity to obtain superior varieties. Important characters in plants that need to be known are quantitative characters. From these characters the superior properties possessed by a variety or clone can be used as a consideration for further selection materials. This research was carried out in July – December 2021 at the IP2TP Cipanas Experimental Garden Protected House, the Ornamental Plant Research Institute. This study aims to obtain superior chrysanthemum clones based on quantitative characters and which have better appearance than the comparison varieties. The selected clones will later be used as prospective parents for seed sources as preparation for the registration of varieties resulting from plant breeding. The research method used was experimental method with Augmented Design which consisted of 47 mutated chrysanthemum clones and 3 comparison varieties, namely Puspita Nusantara, Arosuka Pelangi and Stangkon. The effect of the treatment was analyzed by variance, if the F test at 5% level had a significant difference, then to find out which treatment showed better results, it was continued with the LSI (Least Significant Increase) further test at the 5% level. The results showed that there were significant differences from the test clones in almost all the observed quantitative characters, except for the character of the length of the book, the width of the bunch at the widest point, the number of flowers/stalks and the width of the ribbon flower. Based on the LSI further test, several chrysanthemum clones were obtained which had better quantitative characters than the comparison varieties. The clones that have been selected can then be used as a basic reference for the selection of spray-cut chrysanthemums resulting from gamma ray mutations.